2023
DOI: 10.1017/s1368980023001787
|View full text |Cite
|
Sign up to set email alerts
|

Product promotions in online supermarkets: prevalence of ‘High Fat Sugar Salt’ (HFSS) products and labelling characteristics

Lewis W Wallis,
Sally G Moore

Abstract: Objective: To evaluate the prevalence of ‘High Fat Sugar Salt’ (HFSS) products and front-of-pack nutrition labelling (FOPNL) characteristics across promoted products in UK online supermarkets. Design: A cross-sectional survey conducted (December 2021–January 2022) on promoted products. Data on ingredients, nutritional composition and display of FOPNL were collected from product webpages. The UK’s Nutrient Profiling Model and Multiple Traffic Light criteria were used to determine HFSS sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Another concern raised by participants in our study was the inadequate nutrition labelling for products sold online, with this information often being too small or illegible for reading. These findings support previous studies that have described the availability of nutritional information online as being inconsistently presented ( 33 35 ) . Specifically, a 2021 Canadian study by Lee et al found that although all products examined by the researchers had photos of their nutritional information available, this information was presented in the form of photographs that were illegible 88 % of the time ( 34 ) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another concern raised by participants in our study was the inadequate nutrition labelling for products sold online, with this information often being too small or illegible for reading. These findings support previous studies that have described the availability of nutritional information online as being inconsistently presented ( 33 35 ) . Specifically, a 2021 Canadian study by Lee et al found that although all products examined by the researchers had photos of their nutritional information available, this information was presented in the form of photographs that were illegible 88 % of the time ( 34 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, a 2021 Canadian study by Lee et al found that although all products examined by the researchers had photos of their nutritional information available, this information was presented in the form of photographs that were illegible 88 % of the time ( 34 ) . Similarly, a study of three major UK online supermarkets by Moore and Wallis found that front-of-pack nutrition labelling was displayed inconsistently, with labelling present in photos of 52 % of sampled products ( 35 ) . A UK study by Stones found that although nutritional information was provided through online grocery retail platforms, to locate this information required shoppers to click into a separate window to bring up a product’s description ( 33 ) .…”
Section: Discussionmentioning
confidence: 99%